Consumer' acceptance of electric vehicles in Lisbon - Vrösch, Bob Johan Alexander (2019)
The need for a cleaner environment with less pollution is noticeable. Car brands are anticipating this development and are launching more electric vehicles on the market. This has a positive effect on the market share of electric vehicles, also in Portugal. While there are more electric vehicles visible on the streets, it is unknown if they will completely replace the diesel and gasoline driven vehicles in the future. Many people still see a lot of disadvantages towards electric vehicles. To lower the barriers of buying electric vehicles, governments and organizations are trying to invest in better charging infrastructures and policy incentives. Still, it is not known if these investments will count for a full electric future. The acceptance and awareness of these new vehicles are two factors in this matter that cannot be ignored. This research examines the level of acceptance of electric vehicles by consumers in Lisbon. In order to reach this, the consumer's awareness, perception and preferences towards electric vehicles have been studied. The charging infrastructure and policy incentives play a central role in this research. The research is supported by primary as well as secondary data but mainly depends on the primary data. This primary data collection is done by questionnaires that are answered by people living or working in Lisbon. The outcomes of these questionnaires in combination with the secondary data will provide a valuable perspective of the current situation and can potentially improve the environment of the electric vehicles and drivers in Lisbon.